Pelatihan Packaging (Pengemasan) Sebagai Upaya Meningkatkan Daya Jual Produk UMKM di Lingkungan Kelurahan Pondok Jagung Timur, Serpong Utara, Kota Tangerang Selatan, Banten - Yugi Setyarko; Rina Ayu Vildayanti; Agus Sriyanto (Pusat Riset dan Inovasi Nasional, 2023)
It is felt that community service activities (PKM) in the form of Packaging Training can increase the knowledge and abilities of local residents. So far, many products in Pondok Jagung Timur Subdistrict are not yet known to many people because they do not yet have a brand/label in the form of a business name or product. others who are informative and can promote SME products in Pondok Jagung Timur Village. Good packaging can provide information from the producer to consumers regarding the business and product quality. The lack of knowledge and information of entrepreneurs regarding the matters mentioned above causes SME products in Pondok Jagung Timur Subdistrict to suffer. It is hoped that correct Packaging training will have an impact on optimal results in order to increase income as well as improve the economy of residents through Packaging which is quite significant for small-scale home economic communities. It is hoped that this PKM activity will be able to improve the welfare of the community through packaging in particular and the surrounding community in general so that the positive impact can be felt sustainably.